ダイ47ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 2006 - 成田, 修; ナリタ, オサム; 毛利, 光志; モウリ, コウジ; 中島, 浩一; ナカシマ, コウイチ; 滝沢, 厚詩; タキザワ, アツシ; 押木, 徳明; オシキ, ノリアキ; Narita, Osamu; Mouri, Kouji; et al. (2010)
P(論文) この報告は第47次南極地域観測隊気象部門が,2006年2月1日～2007年1月31日まで昭和基地において行った気象観測結果をまとめたものである.観測方法,測器,統計方法等は第46次隊とほぼ同様である.越冬期間中,特記される気象現象として,次のものがあげられる.1)地上気象観測において,7月の月平均気温が-24.1°Cを記録し,これまでの極値を更新(昨年までの月平均気温の記録は1997年9月の-23.6°C)した.2)昭和基地上空の下部成層圏の気温は,冬から春先にかけて平年より低めに推移した.特に,8-10月にかけ,70 hPa以下の多くの指定気圧面で,これまでの各月の極値を更新する低温を観測した.一方,対流圏においては,10月7～9日にかけてのA級ブリザードの影響で,850 hPa-350 hPaの指定気圧面で,00 UTC観測における10月の高温の極値を更新した.3)昭和基地上空のオゾン全量は,10月17日に114 m atm-cmと,これまでの過去最小を記録(昨年までの最小値は1995年10月6日の128 m atm-cm),月の平均でも10月に137 m atm-cmと,これまでの過去最小を記録し(昨年までの最小値は1996年10月の156 m atm-cm),オゾンホールが現れる前の1980年以前と比べて,半分以下の値となった.また,オゾン量の回復も例年より遅れ,2007年1月となった. This report describes the results of meteorological observations at Syowa Station from February 1st, 2006 to January 31st, 2007, carried out by the Meteorological Observation Team of the 47th Japanese Antarctic Research Expedition (JARE-47). The observation methods, instruments and statistical methods used by JARE-47 were almost the same as those used by the JARE-46 observation team.Remarkable weather phenomena observed during the period of JARE-47 are as follows.1)The monthly mean temperature in July in 2006 at Syowa Station was -24.1°C, which was the lowest record for Syowa Station.2)The temperature of the lower part of the stratosphere over Syowa Station was lower than normal from winter to early spring in 2006. Especially, the minimum temperature at many standard pressure levels under 70 hPa set the lowest record in each month from August to October. On the other hand, in the troposphere, due to the A-class blizzard on 7-10 October, the maximum temperature at the standard pressure level from 850-350 hPa set the highest record in October.3)The amount of total ozone over Syowa Station became lower than or equal to 220 m atm-cm from the end of August to mid-October. The monthly mean amount of total ozone in September was 173 m atm-cm, which was the 4th lowest value in the historical record. On 4th October, the amount of total ozone was 136 m atm-cm, which was the lowest value during JARE-46.The amount of ...